The war / peace dichotomy in the videos of the presidential reelection campaign of Juan Manuel Santos (Colombia). Analysis of legitimation strategies - Mendoza-Escalante, Alfredo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The objective of this research was to analyze the videos of the presidential campaign of Juan Manuel Santos, president reelected in Colombia for the period 2014-2018, to determine and characterize the strategies of legitimation that allowed the adhesion of voters. The present research is mixed, as techniques were used non-participant observation and content analysis, respectively; and the instruments that each offers, such as notebooks and a scheme of analysis that allows to determine the units and categories of analysis. The analysis of the results shows that the legitimation strategies present in the videos delimit the identity of one group (as opposed to another), associate moral values with each one, he uses symbolic frames and rhetorical resources to support the representations that are made of each actor (or group), appeal to arguments of authority and use a prescriptive form, to influence public opinion.